2013
DOI: 10.1590/s1415-790x2013000100003
|View full text |Cite
|
Sign up to set email alerts
|

Dez anos de epidemia do HIV-AIDS em maiores de 60 anos no Distrito Federal - Brasil

Abstract: Introduction: The progressive increase in number of HIV/AIDS cases in old age brings the necessity of studies about the specificities of this phenomenon by region. Objective: To identify the epidemiology in AIDS cases diagnosed in Distrito FederalBrasil, in individuals aged > 60 years old. Methods: We conducted a time serie study with secondary data from SINAN/AIDS for the period

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 10 publications
1
7
0
6
Order By: Relevance
“…Regarding gender, several authors, in agreement with the findings of the present study, have found that men are the most affected, regardless of age 11,13,20,21,28 , although a process of feminization is occurring 15,27,29 . In the study period, it was observed that in three years (2008, 2010 and 2011) the number of notifications was higher among women.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Regarding gender, several authors, in agreement with the findings of the present study, have found that men are the most affected, regardless of age 11,13,20,21,28 , although a process of feminization is occurring 15,27,29 . In the study period, it was observed that in three years (2008, 2010 and 2011) the number of notifications was higher among women.…”
Section: Discussionsupporting
confidence: 92%
“…A greater number of cases was reported in the state among males aged between 60 and 69 years, characterizing them as the predominant segment and probably the "diffusing hub" of the epidemic 11,19 . It should be noted that although there was a reduction in the proportion of men in notified cases in the years 2006 to 2011, this figure increased again from 2012 to 2014.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study on individuals over 60 years of age in the Brazilian capital identified variations in incidence rates over the period from 1999 to 2009. The highest incidence of AIDS was observed between 2000 and 2005 [27]. …”
Section: Discussionmentioning
confidence: 99%
“…A sexualidade faz parte da vida de qualquer indivíduo em qualquer idade, porém, quando relacionada à população idosa, apresenta-se cercada de mitos e crenças (Alencar, & Ciosak, 2014) influenciados por um estereótipo dominante de que idosos são "pessoas assexuadas" (Melo, Leal, Marques, & Marino, 2012). Alguns fatores relacionados à mudança na vida sexual dos idosos incluem os recentes avanços da indústria farmacêutica que permitem o prolongamento da vida sexual ativa e as mudanças de atitudes e comportamentos sexuais, associadas à desmistificação do sexo entre esses indivíduos (Oliveira, Paz, & Melo, 2013). Essa relação do idoso com as novas possibilidades para a atividade sexual ativa traz benefícios para a manutenção de sua qualidade de vida, porém também os tornam pessoas vulneráveis às Infecções Sexualmente Transmissíveis (IST's) (Oliveira, Paz, & Melo, 2013 (Brasil, 2015).…”
Section: Introductionunclassified